Eco-Feminism and Translation: A Critical Reading of Abdel Rahman Munif's Cities of Salt - Jameel Tahmoush; Reem Rostom (CV. Eureka Murakabi Abadi, 2024)
The complexities of language, society, and artistic expressions make literary works like novels difficult to translate. Translators encounter several problems such as cultural subtleties, colloquial idioms, distinctive writing styles, and other poetic aspects. Literary translation is a challenging process that necessitates a profound comprehension of the cultural and contextual nuances of the source material in addition to language proficiency. The Arabic novel Cities of Salt was written by Abdelrahman Munif, and was successfully translated into several languages, including English. Peter Theroux completed the English translation that was initially released in 1987, and he is the one who paved the way for opening up Munif's writing to a wider English-speaking community. The translated version preserves the novel's exploration of the impact of the oil industry on an unnamed Arab Gulf state and its reflection on the profound social, economic, and cultural changes brought about by rapid industrialization. Cities of Salt by Abdul Rahman Munif is a rich exploration of environmental exploitation and gender dynamics in the context of the Arab Gulf region's transformation due to the oil industry. The novel offers a nuanced portrayal of the interconnected challenges faced by communities grappling with rapid industrialization and its far-reaching consequences on both the environment and societal structures, including gender roles. Moreover, this research paper reveals how the exploitation of land mirrors the exploitation of women. The destruction of the environment echoes the silencing and erasure of women's voices and agency. Through an eco-feminist lens, the paper exposes the interconnectedness between the oppression of nature and the oppression of women, both subjected to exploitation, commodification, and dispossession. Because this novel is a quintet, this paper examines excerpts from the first volume, Al-Teeh, which better fit the study’s argument.